Dehydration of Alcohols to Olefins Catalyzed by ZrAPSO-34 Molecular Sieve - Mohammed, Mazin Jasim; Majeed, Najwa Saber; Al-Ani, Mohammed J. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
The lower olefins (Ethylene, propylene, and butylene) are considered the key to the polymeric and petrochemical industries. Dehydration of alcohols to produce light olefins (Methanol-to-olefins reaction) over SAPO-34 molecular sieve has attractedintoigh attention. Modified SAPO-34 zeolite catalyst with Zr metal was successfully prepared under microwave irradiation using morpholine as a structure direct agent. The microwave energy power used was 800 w and the crystallization time was 200 min. The catalyst sample was characterized by XRD, SEM, EDX, BET, FTIR, and TGA analysis. XRD analysis exhibited a typical chabazite structure with high crystallinity. The analysis showed macrocrystalline particles with moderate distribution of silica in the framework structure and a low surface area of 77 m2/g. The vibration peaks of the prepared catalyst showed agreement with the SAPO-34 CHA structure. Catalyst performance towards methanol-to-olefins conversion was performed in a trickle bed reactor with temperatures of 350, 400, 450, and 500 oC at a weight hourly space velocity of 7.7 h-1. The results also reveal at a temperature of 400 oC , that the best olefins selectivity was obtained, reaching 70%, with a longer lifetime of 500 min. methanol conversion was almost 100% at all reaction temperatures. In addition, the effect of methanol concentration was investigated and the results showed that increasing of water content plays a role in increasing catalyst lifetime and preventing coke depositions in pores.